2010
DOI: 10.1258/ebm.2010.010159
|View full text |Cite
|
Sign up to set email alerts
|

Mitotic recombination: a genotoxic effect of the antidepressant citalopram in Aspergillus nidulans

Abstract: This report evaluates the potential of the antidepressant drug citalopram to induce homozygotization of genes previously present in a heterozygous condition, by homologous recombination. In order to address this question, a heterozygous diploid strain of the filamentous fungus Aspergillus nidulans and the homozygotization assay were utilized. Non-cytotoxic concentrations of citalopram (50, 75 and 100 μmol/L) showed a strong recombinogenic effect in A. nidulans, inducing homozygosis of the diploid strain's nutr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…The results of this study are in good agreement with those reported by others, as indicated below. For instance, citalopram induced apoptosis in a human leukemic cell line [4], and it showed a strong recombinogenic effect in Aspergillus nidulans (at 50, 75 and 100 mmol/L) [38]. Furthermore, genotoxic effects of citalopram have been reported as chromosomal aberrations in Chinese hamster lung fibroblasts in vitro, as mutations in Ames assays [39], and as anti-neoplastic properties [40].…”
Section: Resultsmentioning
confidence: 99%
“…The results of this study are in good agreement with those reported by others, as indicated below. For instance, citalopram induced apoptosis in a human leukemic cell line [4], and it showed a strong recombinogenic effect in Aspergillus nidulans (at 50, 75 and 100 mmol/L) [38]. Furthermore, genotoxic effects of citalopram have been reported as chromosomal aberrations in Chinese hamster lung fibroblasts in vitro, as mutations in Ames assays [39], and as anti-neoplastic properties [40].…”
Section: Resultsmentioning
confidence: 99%
“…Conclusively, the finding of the present study indicates that citalopram is a genotoxic agent and produces genetic damages that end up as olive tail moment or MN. These generally positive genotoxic responses with citalopram are in agreement with positive responses for chromosomal aberrations in Chinese hamster lung fibroblasts, bacterial reverse mutation in S. typhimurium TA98 and TA1537 (Snyder et al ., ; Snyder et al ., ), the strong recombinogenic effect of citalopram in A. nidulans diploid cells (Franco et al ., ) and the determination that it is carcinogenic in the small intestine in rats (Snyder et al ., ; Snyder et al ., ). On the other hand, an increase in the mutant frequency was not induced by citalopram at the Hprt locus in mouse lymphoma cells or in a coupled in vitro / in vivo unscheduled DNA synthesis assay in the rat liver.…”
Section: Resultsmentioning
confidence: 99%
“…Based on computer modeling and energy calculations of drug/DNA complexes, the source of genotoxicity caused by citalopram was proposed to be an N-dialkyl group responsible for DNA intercalation (Synder et al , 2006). Citalopram was also shown to induce genotoxicity via DNA strand breaks and mitotic recombination in Aspergillus nidulans and Drosophila melanogaster (Franco et al , 2010; Gürbüzel et al , 2012).…”
Section: Introductionmentioning
confidence: 99%